Arterial Stiffness in Balkan Endemic Nephropathy, an Environmental Form of Aristolochic Acid Nephropathy - Premužić, Vedran; Ivković, Vanja; Leko, Ninoslav; Stipančić, Želimir; Karanović, Sandra; Jelaković, Ana; Vuković Brinar, Ivana; Dika, Živka; Jelaković, Bojan (Frontiers in Cardiovascular Medicine, 2018)
Balkan endemic nephropathy (BEN), an environmental form of aristolochic acid nephropathy is characterized with later onset and milder forms of hypertension (HT). Thus, we hypothesized that arterial stiffness progresses slower in BEN patients resulting in lower CV mortality. A total of 186 hemodialysed (HD) patients (90 BEN, 96 non-BEN; 67.35+13.07 years) were enrolled and followed-up for 25 months. Brachial blood pressure (BP) and pulse wave velocity (PWV) were determined before mid-week dialysis. BEN patients were older (72.±37.1 vs. 62.8±15.1;p<0.001), had shorter duration of HT prior commencement of HD than non-BEN patients (36 vs. 84 months; p<0.001).There were no differences in BP, but BEN patients were treated with less antihypertensive drugs (p<0.01). BEN patients had lower PWV values at baseline and at the end of follow-up period despite being chronologically older (p<0.001). Baseline PWV>10m/s was associated with higher risk for CV mortality (aHR 1.88 [1.42, 2.49]). In multivariate analyses BEN was predictor of lower PWV. During the follow-up period significantly less CV deaths were observed in BEN vs. on-BEN patients (12 vs. 31; p=0.001). CV mortality adjusted for other risk factors was significantly lower in BEN group (aHR 0.17 [0.06, 0.49]). Overall BEN patients had longer mean survival time on HD (22.3 vs.18.2 months; p<0.001). Observed slower vascular aging (i.e. lower PWV) in BEN patients compared to other ESRD patients is related to the later onset of HT and milder stages of HT during predialytic clinical course and better control of BP and phosphate during HD.